2022
DOI: 10.3390/nano12091444
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Micro-Channel Assisted Photonic Crystal Fiber Based Highly Sensitive Sensor for Multi-Analyte Detection

Abstract: A dual-channel propagation controlled photonic crystal fiber (PCF)-based plasmonic sensor was presented to detect multiple analytes simultaneously. Plasmonic micro-channels were placed on the outer surface of the PCF, which facilitates an easy sensing mechanism. The sensor was numerically investigated by the finite element method (FEM) with the perfectly matched layer (PML) boundary conditions. The proposed sensor performances were analyzed based on optimized sensor parameters, such as confinement loss, resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Table 4 shows some of the best sensors of recent papers compared with the proposed sensor. Compared to [26,28,33], the proposed diabetes sensor has a higher AS, and compared to [27][28][29][30][31][32][33], it has a higher WS, which indicates the high sensitivity and unique performance of the proposed sensor.…”
Section: Simulation Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Table 4 shows some of the best sensors of recent papers compared with the proposed sensor. Compared to [26,28,33], the proposed diabetes sensor has a higher AS, and compared to [27][28][29][30][31][32][33], it has a higher WS, which indicates the high sensitivity and unique performance of the proposed sensor.…”
Section: Simulation Results and Discussionmentioning
confidence: 98%
“…Kamrunnahar et al [26] suggested a dual channel propagation controlled PCF. The proposed sensor showed a highest wavelength sensitivity (WS) of 25 000 nm RIU −1 with a maximum sensor resolution (SR) of 4.0 × 10 −6 RIU.…”
Section: Introductionmentioning
confidence: 99%
“…The RI of air is normally 1. The constraint loss is a very important part in the analysis of sensing performance, and its equation is expressed as: [ 20 ] where is the imaginary part of the effective RI.…”
Section: Sensor Design and Theorymentioning
confidence: 99%
“…Recently, Kamrunnahar et al proposed a PCF based dual channel SPR sensor in 2022, where gold was coated as a plasmonic layer to induce SPR. The obtained highest sensitivity of Ch1 was 25000 nm/RIU and 3000 nm/RIU for Ch2 [28]. Moreover, in certain aforementioned studies, filling or coating metals in the inner wall of cladding is challenging, and it is observed that few channels performed unevenly with lower sensitivity.…”
Section: Introductionmentioning
confidence: 98%